Idiopathic midaortic syndrome - DavidSaul; RahulNikam; VinayKandula; AchalaDonuru (Wolters Kluwer Medknow Publications, 2021)
Midaortic syndrome (MAS) is characterized by narrowing of the descending aorta between the distal aortic arch and the aortic bifurcation. We present the case of a 4-year-old male presenting with a murmur and diagnosed with MAS. He was treated with a thoracoabdominal bypass graft.